HIGH SENSITIVITY C-REACTIVE PROTEIN DAN GLUKOSA SAAT MASUK RUMAH SAKIT SEBAGAI PREDIKTOR KEJADIAN MAYOR KARDIOVASKULER(KMK) PADA SINDROMA KORONER AKUT - , Anny Mariyani; , dr. Teguh Triyono, M.Kes, Sp.PK-K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Acute coronary syndrome (ACS) is a collection of clinical symptoms of coronary artery disease with thrombotic disorders that cause atherosclerosis basis atherom plaque. Inflammation contributes importantly in acute atherogenesis and further atherothrombotic. Increased hs-CRP and glucose is a predictor of major adverse cardiac events (MACE) in ACS. However, the result of researchs on the two markers is still not consistent. This study is a prospective cohort study which aims to determine the prognostic value of hs-CRP and glucose on admission in patients with ACS at ICCU Dr.Sardjito Yogyakarta Hospital with a MACE outcomes i. e. death, reinfarction, cardiogenic shock, acute heart failure, ventricular tachycardia and fibrillation (VT/VF), urgent-percutaneous coronary intervention (PCI) were assessed during the 7 days of treatment. Examination of hs-CRP and glucose each with immunoturbidimetric and hexokinase-G6PD method. The results of prognostic valuein the form of relative risk (RR). The study subjects were 60 patients SKA each consisting of 30 patients with hs-CRP >3 mg/L and 30 patients with hs-CRP <3 mg/L